Recent trends on seaweed fractionation for liquid biofuels production - Pablo G. del Río (2020)
Concerns about fossil fuels depletion has led to seek for new sources of energy. The use of marine biomass (seaweed) to produce biofuels presents widely recognized advantages over terrestrial biomasses such as higher production ratio, higher photosynthetic efficiency or carbon-neutral emissions. In here, interesting seaweed sources as a whole or as a residue from seaweed processing industries for biofuel production were identified and their diverse composition and availability compiled. In addition, the pretreatments used for seaweed fractionation were thoroughly revised as this step is pivotal in a seaweed biorefinery for integral biomass valorization and for enabling biomass-to-biofuel economic feasibility processes. Traditional and emerging technologies were revised, with particular emphasis on green technologies, relating pretreatment not only with the type of biomass but also with the final target product(s) and yields. Current hurdles of marine biomass-to-biofuel processes were pinpointed and discussed and future perspectives on the development of these processes given.